Reasons for sports retirement among football and athletics players in Jordan: A comparative study - Sukkarieh, Rawa’ah Adnan; Al-Nahar, Hazem Nouri (Research Journal in Advanced Humanities, 2026)
The study aimed to identify the differences in the reasons for retirement between football players and athletes. The descriptive method was used, and the survey method. The sample consisted of (113) retired players in Jordan, (59) football players, and (54) athletics players. A questionnaire was built for the reasons for retirement consisting of (27) items, using (arithmetic mean, standard deviation, internal consistency, and T-test).  The most important results were: the reasons for retirement among football and athletics players “My income from practicing sports is not enough for me”, the reasons leading to retirement among football players “I retired while I was at the top of my giving to stay in a beautiful shape”, and the reasons leading to retirement among athletics players were “the lack of interest of sports institutions in the country in the type of competitive sport”. The most important conclusions were: There were no differences in the reasons for retirement between football and athletics players, and they were the most critical. The study recommends establishing a fund to help retired players similar to Social Security, and the federation should allocate a sum of money as an end-of-service bonus.